Iron-Catalyzed C3-Formylation of Indoles with Formaldehyde and Aqueous Ammonia under Air - Wang, Qing-Dong; Zhou, Bin; Yang, Jin-Ming; Fang, Dong; Ren, Jiangmeng; Zeng, Bu-Bing (Synlett, 2017)
An efficient iron-catalyzed C3-selective formylation of free (N–H) or N-substituted indoles was developed by employing formaldehyde and aqueous ammonia, with air as the oxidant. This new method gave 3-formylindoles in moderate to excellent yields with fairly short reaction times. Moreover, this procedure for catalytic formylation of indoles can be applied to gram-scale syntheses.
Keywords: iron catalysis; formylation; indoles; indolecarbaldehydes; formaldehyde